PERANCANGAN ARSITEKTUR ENTERPRISE DALAM SISTEM PENILAIAN SANTRI DI LINGKUNGAN LEMBAGA I’DADIYAH MENGGUNAKAN METODE TOGAF - Akhlis Munazilin; Wardatul Gufronia; Syirva Nada Fidya (CV. Denasya Smart Publisher, 2025)
Management of student assessments in Islamic boarding schools, especially at the Madrasah I’dadiyah level, is still largely manual and fragmented, making it difficult to monitor students’ academic development and character effectively (Hidayat, 2019). This study aims to design an Enterprise Architecture for the student assessment system using the TOGAF (The Open Group Architecture Framework) method, known as a standard framework for structured enterprise architecture design (The Open Group, 2018; Lankhorst, 2017). The research approach was carried out through a case study at the Madrasah I’dadiyah Islamic Boarding School Salafiyah Syafi’iyah Sukorejo, which combines business needs analysis, application architecture design, data, and technology (Erl, Khattak, & Buhler, 2017; Nurhadi & Susanto, 2020). The results of the study indicate that the application of TOGAF ADM can produce an integrated system architecture, enabling more efficient, accurate, and easily accessible assessment data management by Islamic boarding school managers. The proposed system also supports data-driven decision-making, facilitates the evaluation of students' academic and moral development, and strengthens educational management within the I'dadiyah environment. This research contributes to the development of an enterprise architecture-based educational information system in Islamic boarding schools.